Trainee Misinterpretations on Pediatric Neuroimaging Studies: Classification, Imaging Analysis, and Outcome Assessment - Guimaraes, C.V.A.; Leach, J.L.; Jones, B.V. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: The scope of trainee misinterpretations on pediatric neuroimaging studies has been incompletely assessed. Our aim was to evaluate the frequency of trainee misinterpretations on neuroimaging exams in children, describe a useful classification system, and assess related patient management or outcome changes. MATERIALS AND METHODS: Pediatric neuroimaging examinations with trainee-dictated reports performed without initial attending radiologist assessment were evaluated for discrepant trainee interpretations by using a search of the RIS. The frequency of discrepant trainee interpretations was calculated and classified on the basis of the type of examination on which the error occurred, the specific type and severity of the discrepancy, and the effect on patient management and outcome. Differences relating to examination type and level of training were also assessed. RESULTS: There were 143 discrepancies on 3496 trainee-read examinations for a discrepancy rate of 4.1%. Most occurred on CT examinations (131; 92%). Most discrepancies (75) were minor but were related to the clinical presentation. Six were major and potentially life-threatening. Thirty-seven were overcalls. Most had no effect on clinical management (97, 68%) or resulted simply in clinical reassessment or imaging follow-up (43, 30%). There was no permanent morbidity or mortality related to the misinterpretations. The most common misinterpretations were related to fractures (28) and ICH (23). CT examinations of the face, orbits, and neck had the highest discrepancy rate (9.4%). Third- and fourth-year residents had a larger discrepancy rate than fellows. CONCLUSIONS: Trainee misinterpretations occur in 4.1% of pediatric neuroimaging examinations with only a small number being life-threatening (0.17%). Detailed analysis of the types of misinterpretations can be used to inform proactive trainee education. CAQCertificate of Added QualificationCIconfidence intervalICHintracranial hemorrhageMRAMR angiographyMRIMR imagingRISradiology information system